Radiographic Study of Mental Foramen in Nepalese Population (Journal of Nobel Medical College, 2019)
Background: Mental foramen is the opening on the anterolateral surface of mandible that marks thetermination of mandibular canal through which mental neurovascular bundle exit. This studyis aimed at determining the location of mental foramen among Nepalese population.Material and Methods: A retrospective study was performed in panoramic radiographs (orthopantomograms) of the patients collected from Department of Oral Medicine and Radiology, Dhulikhel Hospital. Planmeca Promax machine was used to take the radiographs of the patient and Planmeca Roxemis software was used to analyze the digital radiographs. The horizontal position and vertical distance of the mental foramen was evaluated.Results: The study revealed that the most common position of the mental foramen was between first and second premolar (bicuspid) 186 (54.7%) and the second common position was in line with second premolar 122 (35.9%). The mean distance between mental foramen and in fervor border of mandible of male was 12.31 1.64 and female was 10.83 1.19. Independent sample t-test analysis showed a highly significant difference in the distance between mental foramen and inferior border of mandible among male and female (P=0.00).Conclusion: The most common location of mental foramen was between first and second premolar; however, the study revealed the anatomical variation in the positions. So, proper investigation of mental foramen is indispensable before treatment planning to prevent iatrogenic damage to neurovascular bundle.